The Process Algebra Usage for Simulation Purposes - Olishchuk, S.; Volk, M. (ХНУРЭ, 2009)
The Formal description of existing simulation methods with the help of process algebra is considered in the report. Mathematical representation of simulation process by means of operations group performed onto it is given.
Keywords: event; class; alphabet; simulation